Complexity in the therapeutic delivery of RNAi medicines: an analytical challenge. (September 2014) - Colombo, Stefano; Zeng, Xianghui; Ragelle, Héloïse; Foged, Camilla
<x xml:space="preserve">Abstract</x> Introduction: Nucleic acids have witnessed a dramatic acceleration in their therapeutic exploitation and currently represent a growing number of applications in drug development pipelines. However, a more wide-spread development of therapeutics based on nucleic acids is restricted by their poor chemical and enzymatic stability in vivo, lack of cellular uptake and insufficient capability to reach intracellular targets. Areas covered: Advanced formulation of nucleic acids in nano-sized carriers may help unlocking their potential as therapeutic agents. Nano-sized matters own specific features responsible for inducing characteristic interactions with biological molecules and tissues. These properties enable for the enhancement of the nano-formulation's therapeutic efficacy, but on the other hand, the nanomatters interactions in biological fluids are also responsible for adverse effects. The purpose of this review is to reflect on the complexity in the therapeutic delivery of RNA interference-based drugs emerging from the recent clinical experiences and report the actual technological and analytical advances introduced to solve it. Expert opinion: The complexity in the therapeutic delivery of nucleic acids and the heterogeneity of side effects make the interpretation of the therapeutic outcome difficult. Hence the development of analytical approaches applicable in the field of nucleic acid delivery is becoming a major challenge.